Cellular immunity confers transient protection in experimental buruli ulcer following BCG or mycolactone-negative Mycobacterium ulcerans vaccination - Fraga, Alexandra G. (2012)
The authors would like to thank Luís Martins and Miguel Carneiro for laboratory assistance. Author Contributions Conceived and designed the experiments: AGF AGC JP. Performed the experiments: AGF TGM ET. Analyzed the data: AGF. Contributed reagents/materials/analysis tools: FP. Wrote the paper: AGF KH FP MTS AGC JP.